2016
DOI: 10.3390/ijms17030419
|View full text |Cite
|
Sign up to set email alerts
|

LARP6 Meets Collagen mRNA: Specific Regulation of Type I Collagen Expression

Abstract: Type I collagen is the most abundant structural protein in all vertebrates, but its constitutive rate of synthesis is low due to long half-life of the protein (60–70 days). However, several hundred fold increased production of type I collagen is often seen in reparative or reactive fibrosis. The mechanism which is responsible for this dramatic upregulation is complex, including multiple levels of regulation. However, posttranscriptional regulation evidently plays a predominant role. Posttranscriptional regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 104 publications
5
65
0
1
Order By: Relevance
“…Posttranscriptional regulation involves stabilization of collagen mRNAs and regulation of their translation, and is mediated by LARP6 and another RNA‐binding protein, α CP (Bayfield et al . ; Stefanovic ; Zhang & Stefanovic ), our study also showed that LARP6 protein can bind to Col1a2 mRNA (Fig. e, f).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Posttranscriptional regulation involves stabilization of collagen mRNAs and regulation of their translation, and is mediated by LARP6 and another RNA‐binding protein, α CP (Bayfield et al . ; Stefanovic ; Zhang & Stefanovic ), our study also showed that LARP6 protein can bind to Col1a2 mRNA (Fig. e, f).…”
Section: Discussionsupporting
confidence: 76%
“…ª 2017 Japanese Society of Developmental Biologists 2013; Zhang & Stefanovic 2016), our study also showed that LARP6 protein can bind to Col1a2 mRNA (Fig. 3e, f).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Type I collagens are the most abundant component proteins of ECM in human body , and previous studies have shown that Type I collagens account for more than 90% of bone ECM . Type I collagen is a trimeric complex molecule that comprises with two alpha‐1 subunits (COL1A1) and one alpha‐2 subunit (COL1A2) . During the developmental process of growing follicles, collagen content is dynamically changing.…”
Section: Introductionmentioning
confidence: 99%